MODELING THE RISKS OF DEVELOPING AND IMPLEMENTING THE INFRASTRUCTURE PROJECT BASED ON NETWORK PLANNING METHODS - A. I. Denisova (Вестник университета)
A project risk modeling procedure based on the network planning method has been presented. It has been assumed, that each risk can be associated with some positive or negative event or its combination, which can be added to the network model of the project. Depending on the conditions under which risk events occur, various scenarios are developed. For each scenario, a series of Monte Carlo tests is accomplished. The value of the risk is estimated based on the expected values of the traditional financial and temporal characteristics of the project. The described procedure is checked on an illustrative example of the infrastructure project, which consists in laying a section of the pipeline along the seabed. The software implementation of discrete optimization algorithms for the project plan and simulation tests has been implemented in the framework of an automated scenario modeling system using Python.